Usability, durability and regeneration of Ag/ZnO coated microreactor for photocatalytic degradation of methylene blue - Akman, Buğra; Aras, Ömür (Elsevier, 2021)
The microreactor, which was manufactured for the treatment of aqueous methylene blue (MB) solution, was coated with ZnO photocatalyst with different silver content using the spray pyrolysis method. Dye removal from water as a result of photocatalytic reaction at various residence times under UV-A irradiation was investigated. Here, the effect of morphological structures of ZnO-coated surfaces with and without silver on water treatment was observed. In addition, the effects of hydrogen peroxide at different rates on degradation and catalyst strength were investigated. As a result of experiments, 91% methylene blue degradation was obtained with 1% Ag doped ZnO coated microreactor for a residence time of 2.5 minutes. With the addition of 10% hydrogen peroxide, 96% of methylene blue removal was achieved. It was observed that if the photocatalyst coated reactors were operated for more than 40 hours, the removal efficiency decreased to approximately 62% and remained almost constant and again, returned to their previous performance when regenerated by hydrogen peroxide. In this study, for the first time, Ag/ZnO catalyst was coated on aluminum microreactor by spray pyrolysis method and the usability, durability and regeneration of this reactors were evaluated for the photocatalytic degradation of methylene blue under UV-A irradiation. The individual effects of UV radiation, H2O2 content and the catalyst on degradation were also investigated.
Keywords: Photocatalyst; Microreactor; Spray pyrolysis; Methylene blue; Durability; Treatment